PEDAGOGICAL STRATEGIES TO MITIGATE SUICIDAL BEHAVIOR AMONG CHILDREN WITHIN THE CONTEXT OF FAMILY EDUCATION - Свишникова, Н.С.; Мнайдарова, Светлана; Шужебаева, А.И.; Дмитриева, П.Н. (Pedagogy and Psychology, 2023)
The article describes the factors of suicidal risk, in particular, significant experiences associated with close relationships in the family throughout the life of the individual. The results show that conflicting parenting style is closely associated with self-destructive personality behavior. At the moment, there are many approaches that try to explain the true causes of suicide in children and adolescents. Particular attention is paid to the consideration of the family as a factor in the consolidation of auto-aggressive patterns in children and adolescents. The deformation of parent-child relationships and the disorganization of the family as a whole can be considered one of the main socio-psychological causes of suicide. Often the reason for the suicidal risk of a teenager can be an early loss of parents or a violation of constructive relationships with them, an incomplete family, economic problems in the family. Keywords: adolescence; suicidal risk; family disorganization; conflict situations; emotional and behavioral disorders; family psychological support.